The Mutual Influences and Connections between Dalmatia and Croatia at the End of the Middle Ages - Grgin, Borislav (Array, 2007)
The author analyzed mutual connections and influences between Dalmatia and Croatia at he end of the Middle Ages. He concluded that political and military relations were of greater importance then the social and economic links between the two sides.The Ottoman threat was the biggest obstacle for the possible wider communication between the two sides.